PERAN MAJELIS KEHORMATAN NOTARIS TERHADAP AKTA NOTARIS YANG BERINDIKASI PIDANA MENURUT UNDANG - UNDANG NOMOR 2 TAHUN 2014 TENTANG PERUBAHAN UNDANG - UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS - YOPI RACHMAD AFFANDI POHAN (PREMISE LAW JURNAL, 2017)
A notary is a public official whose duty and obligation are to provide service and legal consult to those who need it. In Article 1 figure 1 of UUJN (Notarial Act), it is stated that a Notary is a public official who is authorized to make an authentic deed and who has other authorities as referred to in the law. The penal elements that are frequently encountered by or accused to notaries are document or letter counterfeiting, embezzlement, money laundering and committing perjury under an oath. The research problems are how a notarial deed with indications of penal elements according to the provisions in the prevailing laws and regulations is, how the honorary council of notaries plays their role against the notarial deed with indications of penal elements according to the provisions in the prevailing laws and regulations and how the for of protection by the honorary council of notaries lawsKeywords: Notary, Deed, Penal Indication, Honorary Council of Notaries